2013
DOI: 10.1097/acm.0b013e3182905ceb
|View full text |Cite
|
Sign up to set email alerts
|

Medical Education in the Electronic Medical Record (EMR) Era

Abstract: In the last decade, electronic medical record (EMR) use in academic medical centers has increased. Although many have lauded the clinical and operational benefits of EMRs, few have considered the effect these systems have on medical education. The authors review what has been documented about the effect of EMR use on medical learners through the lens of the Accreditation Council for Graduate Medical Education's six core competencies for medical education. They examine acknowledged benefits and educational risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 43 publications
2
86
0
15
Order By: Relevance
“…"Bloated" notes may be less effective as a communication tool. 12 Additionally, the process of composing a note often stimulates critical thinking and may lead to changes in care. The act of copying forward a previous note and autopopulating data bypasses that process and in effect may suppress critical thinking.…”
Section: Resultsmentioning
confidence: 99%
“…"Bloated" notes may be less effective as a communication tool. 12 Additionally, the process of composing a note often stimulates critical thinking and may lead to changes in care. The act of copying forward a previous note and autopopulating data bypasses that process and in effect may suppress critical thinking.…”
Section: Resultsmentioning
confidence: 99%
“…Tierney et al [30] reviewed the literature on the effects of using EHR on medical learners, and found strong mistrust and concerns that CDS functions in EHR and CPOE system can result in an unacceptably high volume of clinically insignificant alerts and may negatively affect the development of critical thinking and clinical decision-making skills. This negative attitude may affect young graduates and trainees.…”
Section: Discussionmentioning
confidence: 99%
“…7 Clinical decision support (CDS) systems within the EMR link health observations with health knowledge to influence health choices by clinicians. Tierney found that CDS can enhance learners' knowledge at the point of care by providing current information, best practices, and evidence-based care.…”
Section: Can Today's Medical School Faculty Teach Tomorrow's Physiciamentioning
confidence: 99%